1999
DOI: 10.1046/j.1365-2222.1999.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtribe‐specific monoclonal antibodies to Lolium perenne

Abstract: Monoclonal antibodies that are functionally specific to only two grasses can be produced and used to discriminate between related grass species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…In contrast, the GI extract, which showed less than 50% inhibition for Lm immunodominant components, presents in its composition grass pollen tribes (Triticeae and Aveneae) phylogenetically different from L. multiflorum (Poeae). Altogether, these results are consistent with inhibition radioimmunoassay and ELISA studies, using crude extracts of grass pollen of the family Poaceae that showed strong cross-reactivity between their members (1,10,36). Further inhibition experiments should be conducted with purified or recombinant major allergens to confirm the grouping of the individual allergens.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In contrast, the GI extract, which showed less than 50% inhibition for Lm immunodominant components, presents in its composition grass pollen tribes (Triticeae and Aveneae) phylogenetically different from L. multiflorum (Poeae). Altogether, these results are consistent with inhibition radioimmunoassay and ELISA studies, using crude extracts of grass pollen of the family Poaceae that showed strong cross-reactivity between their members (1,10,36). Further inhibition experiments should be conducted with purified or recombinant major allergens to confirm the grouping of the individual allergens.…”
Section: Discussionsupporting
confidence: 84%
“…Studies of the characterization of the major allergens from L. multiflorum are limited, in contrast to a number of studies concerning the characterization, allergenic sensitization and cross-reactivity of pollen allergens from L. perenne and other grasses of the same family of L. multiflorum (1,2,10). In the present study, high homologous inhibition with low IC 50 was observed in ELISA for the detection of IgE in response to the Lm extract, reflecting the specificity of the reaction.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation